Begonia littoralis (Begoniaceae), a new species from North Coast of São Paulo State, Brazil - Miranda, Marcelo Dias; Jacques, Eliane De Lima (Phytotaxa, 2023)
Field research in Submontane Ombrophilous Atlantic Forest in the extreme North Coast of São Paulo State, bordering Rio de Janeiro, has brought us the knowledge of a new species of Begonia (Begoniaceae). The new species is here compared with Begonia erythrobracteata and Begonia fluminensis, by having similar leaf blades which are glabrous adaxially. Description, taxonomic comments, map, photographic plates, illustrations and a provisional IUCN Red List Assessment are provided.